2002
DOI: 10.1080/02673030216000
|View full text |Cite
|
Sign up to set email alerts
|

Moving House, Creating Home: Exploring Residential Mobility

Abstract: This paper begins with a review of the residential mobility literature that arose out of housing and planning policy aimed at decreasing the negative effects of urban transience. The literature identified the range of factors influencing residential mobility, but Rossi's (1955) claim that mobility was a 'natural' outcome of life stage changes became the basis for the majority of this work. Most of this literature arose out of quantitative research approaches but writers drew attention to the inability of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
16

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(73 citation statements)
references
References 34 publications
1
56
0
16
Order By: Relevance
“…Although it appears that disagreement exists in the literature on whether and to what extent this decision making can be described as rational or boundedrational behavior, recent studies tend to view residence and job changes as manifestations of choice from the perspective of an individual agent with a certain socio-economic status at a certain life stage (Dieleman, 2001;Winstanley et al, 2002). Furthermore, it has been suggested that residential and job relocation decisions are highly interrelated with each other and sometimes jointly made, because one choice can significantly affect the 6 outcome of another (Clark and Withers, 1999;van Ommeren et al, 1999 and2000;Kim et al, 2005;Kronenberg and Carree, 2012).…”
Section: Residential and Job Mobility: Manifestation Of Micro Decisionsmentioning
confidence: 99%
“…Although it appears that disagreement exists in the literature on whether and to what extent this decision making can be described as rational or boundedrational behavior, recent studies tend to view residence and job changes as manifestations of choice from the perspective of an individual agent with a certain socio-economic status at a certain life stage (Dieleman, 2001;Winstanley et al, 2002). Furthermore, it has been suggested that residential and job relocation decisions are highly interrelated with each other and sometimes jointly made, because one choice can significantly affect the 6 outcome of another (Clark and Withers, 1999;van Ommeren et al, 1999 and2000;Kim et al, 2005;Kronenberg and Carree, 2012).…”
Section: Residential and Job Mobility: Manifestation Of Micro Decisionsmentioning
confidence: 99%
“…En este sentido, la calidad de la vivienda (Clark y Dieleman, 1996) o la satisfacción con su lugar de ubicación (Winstanley et al, 2002) constituyen factores clave, pero el indicador más claramente relacionado con las decisiones de (in)movilidad es el régimen de tenencia (Speare, 1970;Dieleman y Everaers, 1994;Helderman et al, 2004;Mulder, 2006). En los países donde el alquiler tiene una mayor presencia, sobre todo en los primeros pasos de la carrera residencial, la entrada a la propiedad ha sido considerada como uno de los pasos finales y que marcaba el inicio de periodos de sedentarismo más amplios (Kendig, 1984;Dieleman y Everaers, 1994).…”
Section: El Estado En La Carrera Residencialunclassified
“…No âmbito da vasta bibliografia existente, foram feitas várias tentativas de caracterização/sistematização das diferentes correntes em presença (Dieleman, 2001;Dieleman, 1996;Clark e Dieleman, 1996;Clark e Onaka, 1983;Pickles e Davies, 1991;Bonvalet e Brun, 2003;Brun, 1993;Winstanley, Thorns e Perkins, 2002). No nosso entender, podem identificarse, pelo menos, duas tradições teórico-metodológicas: a do ciclo de vida e da racionalidade económica; e a biográfica e relacional.…”
Section: Uma Apresentação Das Correntes Em Presençaunclassified
“…Por último iremos fazer uma contextualização empírica do caso da AML, caracterizando o processos de metropolização da AML. No fundo, este paper apresenta-se como uma primeira discussão dos dois eixos temáticos (trajectórias residenciais e metropolização) que são centrais para este estudo.T Tr ra aj je ec ct tó ór ri ia as s r re es si id de en nc ci ia ai is s e e M Me et tr ro op po ol li iz za aç çã ão o: : u um ma a a an ná ál li is se e i in nt tr ro od du ut tó ór ri ia a a a p pr ro op pó ós si it to o d da a A AM ML L _ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ __ _ No âmbito da vasta bibliografia existente, foram feitas várias tentativas de caracterização/sistematização das diferentes correntes em presença (Dieleman, 2001;Dieleman, 1996;Clark e Dieleman, 1996;Clark e Onaka, 1983;Pickles e Davies, 1991;Bonvalet e Brun, 2003;Brun, 1993;Winstanley, Thorns e Perkins, 2002). No nosso entender, podem identificarse, pelo menos, duas tradições teórico-metodológicas: a do ciclo de vida e da racionalidade económica; e a biográfica e relacional.…”
unclassified